Engineering Students and Alcohol: Analyzing Consumption Patterns, Influencing Factors, and Implications (JEET) - Binani, Shradha; Singh, Thakur Aryan; Patel, Mihir; Reddy, Nayini Varshitha; Reddy, Dasireddy Bharath (Journal of Engineering Education Transformations, 2025)
Understanding the complex landscape of alcohol consumption patterns among engineering students is crucial for shaping informed interventions and support systems. While prior research has primarily focused on aspects such as the prevalence of alcohol use and its consequences, there exists a significant gap in comprehensively exploring the underlying factors and implications. This research paper aims to bridge this void by exclusively addressing the intricate web of alcohol consumption within the engineering student demographic. The study delves into a multifaceted analysis that encompasses five paramount parameters: social influence, self-regulation, craving, coping strategies, and the environmental context. To achieve this, a meticulously designed survey instrument was deployed to engineering students at an autonomous college during the specified time frame. The collected data underwent rigorous exploratory factor analysis, resulting in the identification of five hypothesized factors that intricately define the landscape of alcohol consumption among engineering students.The reliability of this research instrument was validated through Cronbach’s α values, which exhibited a range from 0.60 to 0.79 and had a minimum and maximum factor loading of 0.49 and 0.62 attesting to the robustness of the instrument. This valuable tool is poised to aid educational institutions in assessing their engineering students’ current levels of awareness concerning alcohol consumption patterns and their underlying factors. Furthermore, it offers a foundation for evidence-based strategies aimed at fostering responsible drinking behaviors and tailored support systems, ultimately enhancing the well-being and academic success of engineering students.